Perioperative Nurse - Anesthesia - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1994)
Over the last ﬁve years the Operating Room Nurses Association of Canada (ORNAC) has become increasingly concerned with the proliferation of roles within the surgical team previously ﬁlled by the operating room registered nurse. The quality of pa- tient care is perceived at risk and the erosion of the operating room nurse's role, with subsequent reductions in nursing positions, is viewed with distress.